Association Between the Frailty and New-Onset Atrial Fibrillation/Flutter Among Elderly Hypertensive Patients - Hang, Fei; Chen, Jieruo; Wang, Zefeng; Yan, Jiafu; Wu, Yongquan (Frontiers in Cardiovascular Medicine, 2022)
Background Frailty was found to be common in patients with atrial fibrillation/flutter (AF), but there was still a lack of evidence regarding the relationship between frailty and new-onset AF. Methods We performed a post hoc analysis of data from the Systolic Blood Pressure Intervention Trial (SPRINT). In addition, we evaluated the relationship between baseline frailty status and new-onset AF in older adult patients with hypertension. Results In total, 7,316 participants were included in our analysis, and a total of 115 new-onset AF occurred during an average of 3.54 years of follow-up. Using SPRINT frailty index criteria, 1,535 fit, 4,041 less fit, and 1,740 frailty were enrolled. Compared with other groups, the incidence of new-onset AF in the frailty group was significantly higher. We constructed three Cox models to assess the relationship between the frailty status (fit group as reference) and new-onset AF. Participants with frailty had a significantly higher risk of new-onset AF compared with the fit group in all the models we used. We combined the fit group and the less fit group into a no frailty group to assess the impact of frailty on new-onset AF in various subgroups. After full adjustment (Model 3), frailty remained associated with the increased risk of new-onset AF compared with the no frailty group [hazard ratio [HR] = 2.09, 95% CI:(1.41, 3.09), p < 0.001]. Additionally, we examined the frailty index as continuous variable to assess the relationship between the frailty index and new-onset AF. The smooth curve showed that log HR appeared to increase linearly. And there was a significant interaction between baseline systolic blood pressure (SBP) categories and frailty on the risk of new-onset AF (p for interaction = 0.030). Conclusion This study found baseline frailty status was a strong independent risk factor for new-onset AF among older adult patients with hypertension. Screening for frailty should be considered in older adult patients with hypertension to prevent new-onset AF.